The association between borderline personality disorder, childhood trauma, neuroticism, and self-rated or clinician-rated functional impairment in euthymic bipolar disorder-1 patients - Aydın, Esat Fahri; Koca Laçin, Tuğba (Frontiers in Psychiatry, 2024)
In this study, we mainly evaluated the associations of borderline personality disorder (BPD), neuroticism, and childhood trauma with the self-rated and clinician-rated overall functional impairment levels of adult euthymic patients with bipolar disorder-1 (BD-1). In addition, we compared patient and healthy control groups regarding the levels of of childhood trauma, neuroticism, BPD and functional impairment.In total, 90 euthymic BD-1 patients and 90 healthy controls were enrolled. The Childhood Trauma Questionnaire-Short Form, the neuroticism subscale of the Eysenck Personality Questionnaire Revised-Abbreviated Form, the Borderline Personality Questionnaire, the Functioning Assessment Short Test, and the Sheehan Disability Scale were administered to the participants.The study revealed that the levels of BPD, neuroticism, emotional abuse, physical abuse, global childhood trauma, self-rated overall functional impairment, all the subdomains of self-rated functional impairment, clinician-rated overall functional impairment, and all the subdomains of clinician-rated functional impairment (except leisure time) were significantly higher in the patients than those in the healthy controls (p < 0.05). Clinician-rated functional impairment levels were significantly correlated with levels of BPD (r = 0.555, p<0.001), neuroticism (r = 0.429, p ˂ 0.001), global childhood trauma (r = 0.391, p <0.001), and all subtypes of childhood trauma except sexual abuse. Self-rated functional impairment levels were significantly correlated with levels of neuroticism (r= 0.289, p = 0.006), physical neglect (r = 0.213, p = 0.044), and BPD (r = 0.557, p < 0.001). In the regression analyses, the self-rated overall functional impairment levels were only significantly associated with the BPD feature levels (β = 0.319, p ˂ 0.001) and the clinician-rated overall functional impairment levels were only significantly associated with the BPD feature levels (β = 0.518, p ˂ 0.001).The present study's findings suggest that BPD features should be addressed in psychosocial interventions aimed at ameliorating functional impairment in patients with BD-1. Only BPD features were associated with self-rated and clinician-rated overall functional impairment levels in the regression analyses in the BD-1 patients. Performing self-rated and clinician-rated functional impairment assessments in the same clinical trial may give rise to relevant findings in the future.